THE ROLE OF HERBAL IMMUNOMODULATORS AS ADJUVANT THERAPY FOR ASYMPTOMATIC AND MILDLY SYMPTOMATIC COVID-19: AN EXPLORATORY CLINICAL STUDY - CR, JAYANTHI; HR, AVINASH; SRIDHAR, SWETHA; K, AKILA; NAMBIAR, SRUTHI; UV, BABU; KUMAWAT, RAJESH (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objectives: The objective of the study is to evaluate herbal immunomodulators (Septilin and Bresol) as a possible adjuvant therapy for the treatment of asymptomatic and mildly symptomatic COVID-19. Methods: Randomized, open-label, comparative clinical study. Subjects were randomized to either arm I [Septilin and Bresol+standard of care (SOC)] or arm II (SOC). This study was registered on CTRI (CTRI/2020/06/025801). Results: Subjects in arm I showed a greater reduction in levels of interleukin-6 tumor necrosis factor-α following treatment than in arm II. Subjects in arm I showed a greater increase in levels of interferon (IFN)-β and IFN-λ than those in arm II. There was a greater reduction in D-dimer in arm I than in arm II subjects (64.28% vs. 35.59%) and all arm I subjects had D-dimer values in the normal range compared to 70% of arm II subjects. There were statistically significant reduction in lactate dehydrogenase and neutrophil-to-lymphocyte ratio in arm I (p<0.016 and p<0.013, respectively). Clinical assessments during the post-illness convalescence period showed significant improvements in fatigue assessment scores and quality of life. Conclusion: This herbal combination as an adjuvant to SOC may provide additional long-term benefits in COVID-19 infection by reducing inflammation. This treatment may offer a good addendum for the management of post-COVID-19 illness.